Perbandingan Hasil Framingham Risk Score (FRS) dan QRISK2 Pada Dewasa Usia Produktif terhadap WHO Chart - Isra Sabrina (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
Background:Framingham Risk Score and QRISK2 are cardiovascular desease (CVD) risk prediction recommended by American Heart Association for early detection of CVD to reduce morbidity and mortality. The primary purpose of this research is to compare the result from FRS and QRISK2 for adult in productive age in Jakarta. Method:This research is conducted using a cross-sectional diagnostic test. We collected primary data from 173 respondents in Wijaya Kusuma, Grogol, Jakarta Barat from September 2018 to November 2018. The data collected are medical history and results from blood pressure, cholesterol, and BMI. All the data entry is calculated by FRS and QRISK2 online calculator, then further analyzed by SPSS program. Results:ROC value for FRS and QRISK2 are 0.60 and 0.69. The sensitivity, spesifity, positive predicting value, and negative predicting value for FRS are 31%, 90%, 35%, and 88%. In another hand, QRISK2 are 58%,81%, 34%, and 91%. This analysis shows that QRISK2 have a higher accuracy compared to FRS. Conclusion:This research shows that there is a difference between FRS and QRISK2 in CVD risk calculation. QRISK2 have higher sensitivity and specifity compared to FRS, but FRS have a better positive and negative predicting value compared to QRISK2. From this research we concluded that use FRS to predict CVD risk in primary care is better compared to QRISK2.